Frontispiece: HN2O2− as a Ligand in Mononuclear Hydrogenhyponitrite‐κ2‐N, O Ruthenium Complexes with Bisphosphane Co‐Ligands. Issue 60 (29th October 2018) - Beck, Daniel; Klüfers, Peter
Abstract : The nitrogen cycle is a process in nature to sustain a living environment. A nitric‐oxide‐to‐nitrous‐oxide step via hyponitrite is easily modeled with marbles but hardly substantiated in its details. There are many hypotheses around the tentative, highly reactive hyponitrite intermediate and its coordination to the iron atoms in the active site of nitric‐oxide reductase. Now, another puzzle piece was obtained by the synthesis and characterization of mononuclear ruthenium complexes, which show the hyponitrite intermediate in its partly protonated HN2 O2 − form. As opposed to its reactivity in the catalytic cycle, trans‐hydrogenhyponitrite, a weak‐field ligand, reveals itself to be stable in the ruthenium environment. For more information, see the Full Paper by P. Klüfers and D. Beck onpage 16019 ff.